Palladium-Catalyzed Selective Synthesis of 3-Hydroxy-2-oxindoles via Cascade C–H Cycloaddition and Oxidation of α-Aminoacetophenones - Liao, Yan-Yan; Xu, Li; Tang, Ri-Yuan; Zheng, Wen-Xu (Synthesis, 2018)
A novel method for the synthesis of 3-hydroxy-2-oxindole (3-hydroxyindolin-2-one) derivatives by palladium-catalyzed tandem C–H cycloaddition and oxidation of α-aminoacetophenone has been developed. In the presence of Pd(OAc)2 and AgOAc, a variety of 3-hydroxy-2-oxindoles were synthesized in moderate yields. Control experiments show that the selective cycloaddition occurs prior to the oxidation is crucial for this successful chemical transformation.
Keywords: palladium; indole; cyclization; oxidation; C–H functionalization